Host heterogeneity in humoral bactericidal activity can be complement independent - Abe, Ryuichiro; Ram-Mohan, Nikhil; Zudock, Elizabeth Jordan; Lewis, Shawna; Carroll, Karen C.; Yang, Samuel (Frontiers in Immunology, 2024)
Humoral bactericidal activity was first recognized nearly a century ago. However, the extent of interindividual heterogeneity and the mechanisms underlying such heterogeneity beyond antibody or complement systems have not been well studied. We analyzed the plasma bactericidal activity of five healthy volunteers against 30 strains of Gram-negative uropathogens, Klebsiella pneumoniae and Escherichia coli, associated with bloodstream infections. We revealed wide variations in plasma bactericidal activities between individuals against various bacterial strains. While individual plasma with higher IgM titers specific to K. pneumoniae strain KP13883 showed more efficient killing of the strain, both IgM and IgG titers for K. pneumoniae strain KPB1 did not correlate well with the killing activity.Complement inhibitor assays elucidated that the complement-mediated killing was not responsible for the inter-individual heterogeneity in either isolate. Furthermore, using MALDI-TOF mass spectrometry on plasmas of 25 healthy individuals, we screened for plasma metabolome components causing the interindividual heterogeneity and identified several small molecules including gangliosides, pediocins, or saponins as candidates. This is the first study to demonstrate the inter-individual heterogeneity of constitutive innate humoral bactericidal function quantitatively and that the heterogeneity can be independent of antibody or the complement system.